PENETAPAN STRATEGI BERSAING BERDASARKAN ANALISIS SWOT DAN MATRIKS STRATEGI PADA UD KUDA TERBANG - Wulandari, Indri; Candrawati, Triesti; Prasetya, Rizky (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2025)
This research aims to determine the competitive strategy of UD Kuda Terbang through SWOT analysis and strategy matrix. The data used are primary data such as observations, interviews, and questionnaires to MSMEs, while secondary data are documentation that includes a brief history of the company, organizational structure, vision and mission. Data obtained from MSMEs will be used as the basis for SWOT analysis. The results showed that MSMEs are in an above-average position according to the values in the IFE and EFE matrices. The SWOT matrix produce several alternative strategies, including market penetration, market development, product development, related diversification, and retrenchment. The IE matrix is in quadrant I, indicating a grow & build position. The GSM matrix is in quadrant I, indicating an aggressive conditions. A comparison of the strategy analysis results of the SWOT, IE, and GSM matrices show that the three best strategies are market penetration, market development, and product development. The QSPM matrix results for these three strategies show that product development strategy is the top priority, with a TAS score of 7.01—the highest compare to the other strategies. UD Kuda Terbang is expected to implement product development strategies, through design innovation, product diversification, or improving products quality.